Perlindungan Hukum Indonesia Bagi Pemegang Hak Atas Pencantuman Merek Terkenal Pada Parfum Lokal - Stefani Adelia Widyani; Febri Noor Hediati (Darma Cendika Catholic University, 2024)
A form of preventive protection against the inclusion of well-known perfume brands on local perfumes is the existence of regulations in the form of provisions in Articles in Law Number 20 of 2016 concerning Brands and Geographical Indications. Apart from that, the regulations include registration and licensing which also includes forms of preventive protection. A form of repressive protection for the owner of a famous perfume is in the form of a claim for compensation or termination of all actions related to the use of the brand or based on criminal prosecution through law enforcement officials. Owners of well-known foreign perfume brands are required to register their brands in Indonesia using the International Registration method according toMadrid Protocol as previously explained. After that, we will enter into a licensing agreement with a local perfume owner who wants to list a famous perfume brand in Indonesia.